IoT Based Battery Car Level - Mohd A’azmi, Muhammad Haziq 'Irfan (Universiti Teknologi PETRONAS, 2020)
Lead-acid battery is generally used for application that require short burst of current to deliver power such as applied in modern cars. The lifetime of this battery reduced due to inefficient use and such operation of charging and discharging that makes it unusable. By having battery monitoring system that able to provide indication of battery condition, such a situation can be avoided. Besides that, an important to consider a number of reliable technique for car battery monitoring system is to prevent car start-up failure. The simplest way of monitoring Lead-acid battery is by estimation of battery state-of-charge (SoC) that usually calculated in percentage forms [1] and can be obtained by referring depth-of-discharge (DoD) curve of the battery [9]. The chosen Lead-acid battery have been tested and the SoC value is estimated. The battery monitoring system consist of voltage sensor that measured the battery voltage precisely, Arduino UNO as a microcontroller, a real-time clock module to accurately provide date and time, Bluetooth module to communicate with smartphone and buck converter to reduced 12V to 5V to power up the system from 12V battery.